Agencia moral de la empresa: el aporte del análisis causal aristotélico - Preziosa, María Marta (2006)
The initial question about the ontological status of the corporation precedes the question about its moral status. The Aristotelian causes are constitutive principles of reality that infl uence each other reciprocally and which we apply to the enterprise to design its anatomy’s ontological structure. The corporation’s material cause is the capability its members have to associate. The formal intrinsic cause is its organization for producing and trading the goods man needs. The extrinsic formal or exemplary cause is the shared mental model. And the corporation’s fi nal cause is its mission. And the common good is the mediate end that gives it sense. The corporation is considered as an entity possessing a certain unity based in the order embodied in the plexus of internal-external relations of the corporation.